The correlation between Diabetes and age-related degeneration and the static and dynamic 3D mechanical distribution of different plantar regions - Yang, Xiong-gang; Hu, Xing-xi; Wang, Qi-yang; Peng, Zhi; Luo, Hao-tian; Lu, Sheng (Frontiers in Endocrinology, 2024)
Purpose: This study aimed to compare the distribution of plantar pressure and anterior-posterior (AP) or medial-lateral (ML) shear forces in healthy younger (HY) people, healthy older (HO) people, and diabetic patients, both in static standing and during gait. Materials and Methods: A total of 20 HY adults, 16 HO adults and 15 diabetic patients were included. The static mechanical distribution measurements included: static horizontal, AP slope plane, and left/right slope standing. Data collected during the gait cycle encompassed the plantar pressure-time integral (PTI), peak pressure (PP), AP/ML shear force-time integral (AP-STI/ML-STI), and AP/ML peak shear force (AP-PS/ML-PS). The plantar surface was segmented into regions including hallux (HL), 2nd~5th toes (T2-5), 1st metatarsal head (M1), 2nd~3rd metatarsal heads (M2-3), 4th~5th metatarsal heads (M4-5), lateral foot arch (LA), and heel regions. Results: The HO group exhibited increased static pressure in M2-3 and heel regions and AP shear force in the entire plantar and M1 regions, in comparison to the HY group. The diabetes group showed increased static pressure in entire plantar, M1, M2-3 and heel regions and AP shear force in the entire plantar, T2-5, M1, M2-3 and heel regions. During gait, the HO group exhibited increased PTI in the whole plantar, T2-5, M2-3, and M4-5 regions, while the diabetes group showed increased PTI in the whole plantar, M1 and M2-3 regions. The HO group showed increased PP in the whole plantar, M1 and heel regions, while decreased in the M2-3 region. The diabetes group showed increased PP in the whole plantar, T2-5, M2-3, M4-5 and heel regions. The HO group showed increased AP-STI in the T2-5, M1, and M2-3 regions, while the diabetes group showed increased AP-STI in the whole plantar, M2-3 and heel regions. Conclusions: Our findings indicate that both static and dynamic plantar pressures and shear forces are significantly greater in diabetic patients and HO individuals compared to HY adults. The most substantial increases was occurred under the M2-3 and heel regions.